Fecal isolation of Pseudomonas aeruginosa from patients with cystic fibrosis. - Agnarsson, U (1989)
Fecal isolation of Pseudomonas aeruginosa was observed in 8 of 10 patients with cystic fibrosis who at the time of sampling also exhibited colonization of the respiratory tract. In contrast, P. aeruginosa cells were isolated at low frequency (9.1%) from the stools of 44 patients with cystic fibrosis with no previous history of chronic colonization. The results of this study suggest that the gastrointestinal tract is not a significant chronic reservoir of P. aeruginosa prior to pulmonary colonization.